2015
DOI: 10.1002/2015jc011131
|View full text |Cite
|
Sign up to set email alerts
|

Observed enhanced internal tides in winter near the Luzon Strait

Abstract: Seasonal characteristics and nonlinear interaction of internal tides (ITs) near the Luzon Strait in the northeastern South China Sea are investigated using 285 day, in situ observation data. It is found that ITs, which are dominated by the first‐mode wave throughout the year, are the strongest in subsurface layer. Baroclinic incoherent diurnal (semidiurnal) variance accounts for about 85.7% (78.3%) of diurnal (semidiurnal) ITs. The amplitude and seasonal variation of the diurnal ITs are more prominent than tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…However, in other cases (e.g., Nameless, ConChan and Mindule in the subsurface layer), fortnightly oscillation was very irregular, and low‐frequency modulation was found, such as in typhoon ConChan, when the period of the spring‐neap tide was nearly one month (the white vertical arrows in Figures c and f indicate the occurrence of the spring tides). This low‐frequency modulation may be due to the enhanced incoherent component of diurnal ITs, which is induced by nonlinear interaction, variable stratification or mesoscale activity (Liu et al, ; Park et al, ). Moreover, results showed that the strong power signals around the near‐inertial period after the passage of each typhoon mainly concentrate in the subsurface layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in other cases (e.g., Nameless, ConChan and Mindule in the subsurface layer), fortnightly oscillation was very irregular, and low‐frequency modulation was found, such as in typhoon ConChan, when the period of the spring‐neap tide was nearly one month (the white vertical arrows in Figures c and f indicate the occurrence of the spring tides). This low‐frequency modulation may be due to the enhanced incoherent component of diurnal ITs, which is induced by nonlinear interaction, variable stratification or mesoscale activity (Liu et al, ; Park et al, ). Moreover, results showed that the strong power signals around the near‐inertial period after the passage of each typhoon mainly concentrate in the subsurface layer.…”
Section: Resultsmentioning
confidence: 99%
“…While strong nonlinear interaction appeared in the subsurface layer, there remains the question as to why the fD 1 currents were not also significantly enhanced in the upper and lower layers, that is, could the fD 1 waves in the subsurface layer after the passage of a typhoon propagate downward like the D 2 waves induced by nonlinear interaction in Liu et al (2015)? The wave number rotary spectra of NICs and fD 1 currents after the passage of a typhoon are shown in Figure 11.…”
Section: 1029/2017jc013555mentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al . [] also observed enhanced internal tides in winter near the Luzon Strait, which was 1.6 times as large as that in spring, and they considered both Kuroshio intrusion and nonlinear interaction of internal tides contributed to the strong internal tides in winter near the Luzon Strait. The strong internal tides in winter are a likely candidate for the high‐level diapycnal diffusivity in winter.…”
Section: Discussion and Summarymentioning
confidence: 99%